2020
DOI: 10.3390/biom10030492
|View full text |Cite
|
Sign up to set email alerts
|

Induction of p53-Dependent Apoptosis by Prostaglandin A2

Abstract: Prostaglandin (PG) A2, one of cyclopentenone PGs, is known to induce activation of apoptosis in various cancer cells. Although PGA2 has been reported to cause activation of apoptosis by altering the expression of apoptosis-related genes, the role of p53, one of the most critical pro-apoptotic genes, on PGA2-induced apoptosis has not been clarified yet. To address this issue, we compared the apoptosis in HCT116 p53 null cells (HCT116 p53-/-) to that in HCT116 cells containing the wild type p53 gene. Cell death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
(49 reference statements)
1
15
0
1
Order By: Relevance
“…Cyclopentenone prostaglandins such as PGA1 and PGA2 have been found to inactivate p53-dependent transcription and induce p53-independent apoptotic cell death ( Lee et al, 2020 ). More specifically, PGA1 appears to induce apoptosis in mammalian cells by specifically binding to H- and N-Ras on endomembranes and activating them ( Anta et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclopentenone prostaglandins such as PGA1 and PGA2 have been found to inactivate p53-dependent transcription and induce p53-independent apoptotic cell death ( Lee et al, 2020 ). More specifically, PGA1 appears to induce apoptosis in mammalian cells by specifically binding to H- and N-Ras on endomembranes and activating them ( Anta et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, PGA 2 was shown to induce apoptosis dependent on DR5, whose expression was stimulated by DNA-dependent protein kinase (DNA-PK)-p53 pathway in HCT116 cells [16]. However, we also observed that PGA 2 induced apoptosis in HCT116 p53 null cells (HCT116 p53 −/−).…”
Section: Introductionmentioning
confidence: 41%
“…Steroids, such as prostaglandin A2 (PGA2) and prostaglandin J2 (PGJ20), were overexpressed after hyperthermal ablation. Some researchers have reported that PGA2 might induce apoptosis in cancer cells via activation of tumor suppressor protein 53, which is one of the most crucial tumor suppressor genes [ 38 ]. The A and J series of prostaglandins are both characterized by reactive alpha, beta-unsaturated carbonyl compounds, which might be critical for the control of DNA-binding activity [ 39 ].…”
Section: Discussionmentioning
confidence: 99%